Perceptions of fairness and effectiveness of performance appraisal as related to work behaviour - Chai, Cherry Ling Ling. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Perception of fairness and effectiveness of the appraisal system is important as it determines work behaviour in the workplace. Perceived fairness will lead employees to show positive work behaviour. Generally this study aims to look into components of fairness and effectiveness of the appraisal system (rating system, feedback from the supervisor, accountability, effective communication, involvement of employee in objective setting and organizational fairness) as related to employee work behaviour in a telecommunications company. The objective of this study is to identify the relationship between the employees' perception of components of fairness and effectiveness and the supervisors' perception of the impact of the appraisal system on work behaviour. This study chose the survey method as the research design using convenience sampling with a sample of 437 respondents out of 1000 non-executive employees. The instruments used are questionnaires and interviews which will then be analysed with descriptive statistics such as frequencies and Pearson correlation using SPSS. Results of this study show that there is a positive and significant relationship between employees' perception of the appraisal system and how supervisors perceive the impacts of the performance appraisal on work behaviour. This result further supports past research that perceived fairness of the appraisal system has a positive impact on work performance.